Partial cystectomy and bilateral ureteroneocystostomy for resection of invasive transitional cell carcinoma involving the trigone area of the bladder in a dog - Case report - Ribeiro, J. O. [UNESP]; Wittmaack, M. C.N. [UNESP]; Gomide, P. R.S. [UNESP]; Montanhim, G. L. [UNESP]; Sembenelli, G. [UNESP]; Ferreira, M. G.P.A. [UNESP]; Cosentino, P. D.; de Nardi, A. B. [UNESP]; Moraes, P. C. [UNESP] (My University, 2018)
This study aims to report the technique of partial cystectomy and bilateral ureteral reimplantation for resection of transitional cell carcinoma (TCC) in the trigone region of the bladder and the long-term follow-up in a Bernesse Mountain dog. The proposed surgical technique was considered viable and a potential treatment option for TCC in bladder trigone, with benefits regarding the prevention of urinary tract obstruction due to neoplastic growth and local removal of the primary tumor, which may limit or delay the spread of the disease even without adjuvant chemotherapy. The main disadvantages related to the described technique are ureteral stricture, intermittent cystitis and local relapse. However, the results are acceptable considering the long-term survival of 610 days in the case described.
Keywords: Ureteral reimplantation; Urinary bladder; Urothelial carcinoma